Design and Performance Analysis of Spiral Microchannels for Efficient Particle Separation Using Inertial Microfluidics - Ozyilmaz, Eda; Ilis, Gamze Gediz (Mdpi, 2025)
Accurate separation in microfluidic devices is crucial for biomedical applications; however, enhancing their performance remains challenging due to computational and experimental constraints. This study aims to optimize microfluidic devices by systematically refining spiral microchannel configurations for the segregation of circulating tumor cells (CTCs) and red blood cells (RBCs) through detailed variable analysis and resource-efficient techniques. The spiral design was developed into six variations, considering loop numbers (2, 3, and 4), aspect ratios (2.333, 3.333, and 5), spiral radii (5, 6, and 7 mm), flow rates (1.5, 2, and 3 mL/min), surface roughness levels (0, 0.5, and 1 mu m), and particle sizes (12, 18, and 24 mu m). Simulations were conducted in COMSOL Multiphysics and evaluated using the Taguchi method to determine the optimal configuration, reducing the analysis set from 216 to 27 through an efficient experimental design approach. The results identified the optimal structure as having an aspect ratio of 3.333, four loops, a spiral radius of 6-7 mm, a flow rate of 3 mL/min, a surface roughness of 1 mu m, and a particle diameter of 24 mu m. Among the evaluated parameters, aspect ratio (61.2%) had the most significant impact, followed by the number of loops (13.9%) and flow rate (9.4%). The optimized design demonstrated high separation efficiency and purity, achieving 97.5% and 97.6%, respectively. The fabrication process involved 3D-printing the channel mold, followed by polydimethylsiloxane (PDMS) casting, validating the durability and scalability of the proposed design. This study integrates simulation and experimental results, providing a robust framework for developing next-generation microfluidic devices and advancing diagnostic and targeted therapeutic applications.
Keywords: microfluidic device; particle separation; inertial microfluidics; spiral microchannels; performance analysis; Taguchi method; design optimization